Geological Mapping and Assessment for Measurement the Electric Grid Transmission Lines in West Sumatera Area, Indonesia - Kausarian, Husnul; Batara, Batara; Eka Putra, Dewandra Bagus; Suryadi, Adi; Lubis, Muhammad Zainuddin (International Journal on Advanced Science, Engineering and Information Technology, 2018)
Energy needs in Indonesia increase rapidly, and Indonesian Government pays serious attention to this program. One of this program application is to build the new power plant and its transmission line in Alam Pauh Duo, District of Solok Selatan. The geological condition in this area consists of Geomorphology Units of the Hills and High Geomorphological Units with the altitude of about 900-500m (meters) with lithology of volcanic rock and intrusion of granite and granodiorite. The review survey (checking and renaissance) was applied for geological mapping in this study by a road sweeping or tracking using a handheld GPS. The result of this mapping and assessment are the coordinate values of the markers or dividing marks that are already available and scattered in each location point. The final result is a map that has a description of the location of Land Power Plant and Transmission Tower. There are 15 transmission towers planned for the builders as well as the power plant (GI). The required land area of each transmission tower is about 15x15 m (meters) up to 20x20 m and the land area for 3ha (hectare) power plant (GI) development. Then the distance between each tower transmission approximately 200 meters.